Question
upstudy study bank question image url

2. \( \frac{\sin x+\sin 2 x}{1+\cos x+\cos 2 x}=\tan x \)

Ask by Best Blake. in South Africa
Feb 28,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions to the equation \( \frac{\sin x+\sin 2x}{1+\cos x+\cos 2x}=\tan x \) are all real numbers except \( x = \frac{\pi}{2} + k\pi \), \( x = \frac{2\pi}{3} + 2k\pi \), and \( x = \frac{4\pi}{3} + 2k\pi \) for any integer \( k \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

To solve the equation \( \frac{\sin x+\sin 2 x}{1+\cos x+\cos 2 x}=\tan x \), let's first rewrite both sides in a more manageable form. The left-hand side can be expressed using the double angle identity for sine: \[ \sin 2x = 2 \sin x \cos x. \] Thus, the left side becomes: \[ \frac{\sin x + 2 \sin x \cos x}{1 + \cos x + \cos 2x}. \] Now, we know that \( \cos 2x = 2\cos^2 x - 1 \), so we substitute that into the denominator: \[ 1 + \cos x + (2 \cos^2 x - 1) = \cos x + 2 \cos^2 x. \] So now the left-hand side can be represented as: \[ \frac{\sin x(1 + 2 \cos x)}{\cos x + 2 \cos^2 x}. \] For the right-hand side, \( \tan x \) is defined as \( \frac{\sin x}{\cos x} \). Thus, the equation becomes: \[ \frac{\sin x(1 + 2 \cos x)}{\cos x + 2 \cos^2 x} = \frac{\sin x}{\cos x}. \] Assuming \(\sin x \neq 0\) (we will handle that case separately), we can divide both sides by \(\sin x\): \[ \frac{1 + 2 \cos x}{\cos x + 2 \cos^2 x} = \frac{1}{\cos x}. \] Cross-multiplying gives us: \[ (1 + 2 \cos x) \cos x = \cos x + 2 \cos^2 x. \] Expanding both sides results in: \[ \cos x + 2 \cos^2 x = \cos x + 2 \cos^2 x. \] This is always true, suggesting that all \(x\) satisfying \(\sin x \neq 0\) are valid solutions. Now, let's check the case when \(\sin x = 0\), which occurs at \(x = n\pi\) for \(n\) an integer. For \(x = n\pi\): \[ \tan(n\pi) = 0, \] and the left-hand side: \[ \frac{\sin(n\pi) + \sin(2n\pi)}{1 + \cos(n\pi) + \cos(2n\pi)} = \frac{0}{1 + (-1)^n + 1} = 0. \] Hence, the equation holds for \(x = n\pi\) as well. In conclusion, the solutions to the equation are: \[ x = n\pi \quad (n \in \mathbb{Z}). \]

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy